GAMBARAN SURVEILANS KASUS LEPTOSPIROSIS BERDASARKAN PELAKSANAAN SISTEM SURVEILANS DI KOTA SEMARANG (STUDI KASUS DI PUSKESMAS DAN DINAS KESEHATAN KOTA SEMARANG) - Frima Rifqi Azzahroh; Mateus Sakundarno Adi; Ari Udiyono; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Leptospirosis is an infectious disease caused by pathogenic leptospira bacteria, which is transmitted directly or indirectly from animals to humans, so the disease is classified in zoonoses. Leptospirosis is a zoonotic disease that is most widely spread in the world. The disease is becoming one of the leading causes of death in the city of Semarang. Control program of cases leptospirosis in Semarang continues to happen every year, but the number of cases continues to exist and increasing every year. The purpose of this study to describe the surveillance of cases leptospirosis by implementation of a surveillance system in the city of Semarang. This type of research is descriptive qualitative in-depth interviews. The research sample as many as 12 research subjects using purposive sampling technique. The results showed that in terms of data collection all recipients have collected all the elements of data collection and reporting of data. In terms of data processing of cases, most of the study subjects had done all the data processing amount of suspect cases, probable, and confirm using descriptive analysis. The detection method used is RDT (Rapid Diagnostic Test) with Leptotek. Dissemination of information and feedback by all study subjects. Follow-up and evaluation has been carried out intensively by Semarang City Health Office. It is advisable to Semarang City Health Office to conduct training on surveillance in all Primary Health Care in Semarang City and necessary analytical analysis and utilization of GIS software and SPSS applications.